Determinants of government debt portfolio management: A VECM analysis of Indonesia’s fiscal dynamics - Sumantri, Joko; Akhmadi, Muhammad Heru; Kusumawati, Rahayu; Purnomoputro, Ajik; Setiawan, M Rudy (WIM Solusi Prima, 2025)
This paper explores the macroeconomic determinants shaping the composition of Indonesia’s sovereign debt portfolio, distinguishing between foreign loans, government securities, and sukuk instruments. Using quarterly data from 2010 to 2025 and a Vector Error Correction Model (VECM), the study reveals robust long-run cointegration between key macro variables and debt composition. Exchange rate stability, global interest rate dynamics, and fiscal policy adjustments emerge as dominant drivers. Policy implications underscore the importance of active debt diversification and macroprudential coordination to enhance fiscal resilience. Employing the Vector Error Correction Model (VECM), the analysis examines the impact of the exchange rate (X1), LIBOR (X2), SIBOR (X3), U.S. Prime Rate (X4), Japan Prime Rate (X5), foreign exchange reserves (X6), inflation rate (X7), and GDP growth rate (X8) on the allocation of foreign loans (Y1), government debt securities (Y2), and state sharia securities (Y3) over the period 2010–2025. The findings reveal that the relationships between the dependent variables (Y1, Y2, Y3) and the macroeconomic indicators (X1–X8) are both dynamic and heterogeneous in the short and long term. These results underscore that the effectiveness of economic policy is not solely dependent on direct interventions targeting debt instruments, but also on the government's ability to manage long-term adjustment mechanisms and short-term transmission channels, particularly through key variables such as X5, X3, and X2.